2010
DOI: 10.1002/pssb.200945569
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate and temperature on the shape of deposited Fe, Co, and FeCo nanoparticles

Abstract: In situ scanning tunneling measurements have been carried out on mass-filtered supported Fe, Co, and FeCo alloy nanoparticles with diameters between 4 and 14 nm. These nanoparticles are prepared from the gas phase using a continuously working cluster source and are subsequently deposited on bare W(110) and Ni(111)/W(110) surfaces. The size and the crystallographic structure before deposition are determined by high resolution transmission electron microscopy (HRTEM), the height of the nanoparticles on the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…The low kinetic energy per atom (usually less than 0.1 eV per atom) of the nanoparticles allows soft-landing deposition experiments well below the fragmentation threshold [39]. Accordingly, recent STM studies revealed that the shape of larger particles ( D > 4 nm) is only weakly affected when being deposited onto single crystalline substrates, i.e., the height of supported particles as measured with STM corresponds well with the size being determined by TEM [28,4041]. This is a particular strength of soft-landing techniques.…”
Section: Methodsmentioning
confidence: 94%
“…The low kinetic energy per atom (usually less than 0.1 eV per atom) of the nanoparticles allows soft-landing deposition experiments well below the fragmentation threshold [39]. Accordingly, recent STM studies revealed that the shape of larger particles ( D > 4 nm) is only weakly affected when being deposited onto single crystalline substrates, i.e., the height of supported particles as measured with STM corresponds well with the size being determined by TEM [28,4041]. This is a particular strength of soft-landing techniques.…”
Section: Methodsmentioning
confidence: 94%
“…Na área de química, a deposição controlada de nanopartículas em superfícies pode ser feita para a construção de sítios orientados para atuarem como catalisadores em reações de interesse [135], bem como na fabricação de tintas magnéticas [16,17]. Em eletrônica, recentes estudos experimentais envolvendo nanopartículas de ferro e cobalto depositadas em superfícies relatam distorções estruturais que podem ser controladas através da direção cristalina do corte da superfície [136]. Mecanismos como este podem ser usados no futuro para a construção bottom-up de novos dispositivos magnéticos.…”
Section: O N S I D E R a ç õ E S F I N A I S E P E R S P E C T I Va Sunclassified